2018
DOI: 10.1002/ajhb.23132
|View full text |Cite
|
Sign up to set email alerts
|

Midfacial growth patterns in males from newborn to 5 years old based on computed tomography

Abstract: Variables commonly assigned to the same unit of the facial skeleton can exhibit rather different growth trends, but some measurements display seemingly coordinated patterns of growth change. The level of interindividual variation of most measurements is stable after the second half of the first year of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 97 publications
2
22
0
1
Order By: Relevance
“…) and present higher morphological variability (Evteev et al. ), especially in older age groups as sexual dimorphism is inducing morphological changes in those areas (Freidline et al. ; Holton et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) and present higher morphological variability (Evteev et al. ), especially in older age groups as sexual dimorphism is inducing morphological changes in those areas (Freidline et al. ; Holton et al.…”
Section: Discussionmentioning
confidence: 99%
“…6), as they 'diffuse' mechanical loads across the skull (Popowics & Herring, 2007). Areas such as the upper face and nasal region that are under fewer functional constraints show more consistently forming fields (Martinez-Maza et al 2013) and present higher morphological variability (Evteev et al 2018), especially in older age groups as sexual dimorphism is inducing morphological changes in those areas (Freidline et al 2016;Holton et al 2016). Although interindividual variability in the percentages of bone resorption is high, particularly in younger age groups, overall the general patterns of bone modeling remain very similar from age groups 2-4 in this European sample (Fig.…”
Section: Interindividual and Intrapopulation Variabilitymentioning
confidence: 99%
“…The HMH‐based method is also widely used in geometric morphometrics due to its accuracy (Bauer, Benazzi, Darlas, & Harvati, ; Coquerelle et al, ; Evteev, Anikin, & Satanin, ; Gröning, Fagan, & O’Higgins, , ; Rivera & Mirazón Lahr, ; Senck & Coquerelle, ; Stoessel, Gunz, David, & Spoor, ). In the original paper describing this approach, the means of 10 HMH values along various randomly selected slices were used to obtain the global threshold (Coleman & Colbert, ).…”
Section: Discussionmentioning
confidence: 99%
“…This study suggested that at least 100 and ideally thousands of randomly drawn lines should be used when selecting a global threshold for skulls. Otherwise, lines should be drawn on pre‐defined regions like as Evteev et al () instead of random selection. Thus, it might be difficult to apply this method to a complex object such as a skull unless to some extent high‐resolution images are available.…”
Section: Discussionmentioning
confidence: 99%
“…Ê òàêîìó aeå âûâîäó ïðèõîäèò è àâñòðàëèéñêèé ó÷åíûé Ê. Ñòåôàí, êîòîðûé â ñâîåé ñòàòüå ñîïîñòàâèë ÷åòûðå ñàìûõ ðàñïðîñòðàíåííûõ ìåòîäèêè âîññòàíîâëåíèÿ íîñîâîé îáëàñòè. Èññëåäîâàòåëüñêèì ìàòåðèàëîì ïîñëóaeèëè 59 ëàòåðàëüíûõ ðåíòãåíîãðàìì, 29 ìóaeñêèõ è 30 aeåíñêèõ, ïðèíàäëåaeàùèõ ñîâðåìåííûì áåëûì àâñòðàëèéöàì [Stephan, 2003] [Evteev et al, 2018].…”
unclassified